Correction to: Environmental occurrence and assessment of organic pollutants in surface sediments of South Peninsular Malaysia (Environmental Geochemistry and Health, (2024), 46, 4, (140), 10.1007/s10653-024-01916-5) - Alkhadher S.A.A.; Sidek L.M.; Zakaria M.P.; AL-Garadi M.A.; Suratman S. (Springer, 2025)
Correction to: Environmental Geochemistry and Health (2024) 46:140https://doi.org/10.1007/s10653-024-01916-5. The acknowledgement section is removed and its content is moved under the funding section. The sentence ?The authors also extend their appreciation to the Deputyship for Research and Innovation, ?Ministry of Education? in Saudi Arabia for funding this research (IFKSUOR3-416-2).? is corrected as ?The research also was funded by Researchers Supporting Project number (RSPD2024R690), King Saud University, Riyadh, Saudi Arabia.? in the funding section. The original article has been corrected. ? The Author(s), under exclusive licence to Springer Nature B.V. 2024.